Analisis pengaruh nilai tukar, pertumbuhan ekonomi dan tenaga kerja terhadap ekspor Indonesia dan Malaysia ke China. - Mustika, Candra; Achmad, Erni (Jurnal Paradigma Ekonomika, 2021)
The purpose of this study was to determine and analyze the development of exchange rates, labor, and economic growth, and exports of Indonesia and Malaysia to China from 1993 to 2015 and to analyze the effect of exchange rates, labor, and economic growth on Indonesian and Malaysian exports to China from 1993 to 2015 Based on the results of research The development of Indonesian exports to China fluctuated or fluctuated during the period 1993 to 2015 with an average of 13.95%, while the rupiah exchange rate against the United States dollar and economic growth also fluctuated the average growth the rupiah exchange rate against the United States dollar was 14.52%, and the average economic growth of 4.69% labor also fluctuated with an average growth of 1.72%. Based on the results of the panel data regression shows the exchange rate variable has a significant negative effect on exports to China, the labor variable has a positive and significant effect on exports to China, while the economic growth variable has no significant effect on exports to China. Â